مناهج الاختيار عند ابن خالويه في إعراب القراءات السبع وعللها - دحماني، أسماء (عبدالفتاح ادريس, 2017)
This report delt with the subject of choosing syllabus By ibn khalawayh in the conjugation of the seven lectures and he gave justification. First he delt with the tradiction of ibn khalawayh and gave the definitions by writing the seven lectures conjugation and justifications, and he delt also to the definition of the chois and its condition, then this study showed the grammar that ibn khalawayh used in his choices, si that his syllabus make deference from the source syllabus that he based on in the group lecture and why thèse verses and the explanation syllabus consontrated on giving detailes on the verses and the language syllabus grouped the grammar and syntax and the side of intonation. To conclude i reminded the results that I found with some proposals and focused in this research on descriptive and analysing syllabus.
تناول هذا المقال موضوع مناهج الاختيار عند ابن خالويه في إعراب القراءات السبع وعللها، حيث تطرقت أولا إلى ترجمة ابن خالويه والتعريف بكتابه إعراب القراءات السبع وعللها، كما تعرضت إلى تعريف الاختيار وشروطه، ثم وضحت الدراسة القواعد التي انتهجها ابن خالويه في اختياراته، فتنوعت بين المنهج الأثري الذي اعتمد فيه على قراءة الجماعة وأسباب النزول وسياق الآيات والمنهج المعنوي الذي ركز فيه على تفسير الآيات ومنهج لغوي جمع فيه بين النحو والصرف وحتى الجانب الصوتي، وأتممت بخاتمة ذكرت فيها أهم النتائج المتوصل إليها مع بعض الاقتراحات، معتمدة في البحث على المنهج الوصفي التحليلي.
Keywords: القراءات القرآنية -- القراءات السبع -- النحو العربي -- التراكيب الصرفية -- ابن خالويه، أبو عبدالله الحسين بن أحمد، ت. 370 هـ